Violence of Police and Army in Roy’s The Ministry of Utmost Happiness:A Thematic Study - Kumar, Rajneesh (International Journal of Psychosocial Rehabilitation, 2020)
The present research paper attempts to explore the violence of police and army in Arundhati Roy’s second novel The Ministry of Utmost Happiness. Sheer ferocityof the police and army is indeed a very grave issue of misuse of power. It shatters the morale of the victims in such a manner that it becomes significantly complex for them to stand on their feet afterwards. It is not only a social but also a criminal matter, which should be dealt with iron fist. But due to its under-reporting, this problem is becoming exceptionally severe with every passing day.The novelist exposes the social perspective with the help of physical and psychological violence. She doesn’t mince words when presents the police and army violence against men, women, children and even the transgender community. In order to draw a comprehensive picture she has very skillfully thrown light upon the multiple instances of violence against the underdogs. Indian society has turned up to be anevident platform of different types of brutalities. Arundhati Roy has shown various categories of violence against the poor, Dalits, women, children, unemployed and even transgenders, but this paper deals exclusively with the atrocities practiced by the police and army.